2011
DOI: 10.1007/s00259-011-1986-7
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxyglucose positron emission tomography pulmonary imaging in idiopathic pulmonary fibrosis is reproducible: implications for future clinical trials

Abstract: This study demonstrated that there is excellent short-term reproducibility in pulmonary (18)F-FDG uptake in patients with IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 33 publications
1
38
0
3
Order By: Relevance
“…The 111 In-DTPA-A20FMDV2 is known to bind to human avb6 integrins in vitro and in vivo (30,31) and 111 In-labeled peptides are widely used in clinical practice. Moreover, 18 F-A20FMDV2 has been used in vivo for successful PET imaging of avb6 on human xenografts (30), and PET/CT scans have previously been obtained for IPF patients (22,23). Thus, SPECT/CT or PET/CT with radiolabeled A20FMDV2 can offer valuable new imaging modalities for stratifying patients with IPF, although at the present time SPECT is more widely available and less costly than PET imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 111 In-DTPA-A20FMDV2 is known to bind to human avb6 integrins in vitro and in vivo (30,31) and 111 In-labeled peptides are widely used in clinical practice. Moreover, 18 F-A20FMDV2 has been used in vivo for successful PET imaging of avb6 on human xenografts (30), and PET/CT scans have previously been obtained for IPF patients (22,23). Thus, SPECT/CT or PET/CT with radiolabeled A20FMDV2 can offer valuable new imaging modalities for stratifying patients with IPF, although at the present time SPECT is more widely available and less costly than PET imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies have used PET tracers including 18 F-FDG and 68 Ga-labeled somatostatin analogs that bind the somatostatin receptor (21,22). Pulmonary uptake of both these radiotracers is increased in IPF patients, and lung 18 F-FDG levels have been related to disease severity (23).…”
mentioning
confidence: 99%
“…A few recent studies evaluated the use of PET techniques in IPF patients (7)(8)(9)(10)(11)(12)(13)(14)(15), mostly with 18 F-FDG as a tracer of glucose uptake and metabolism. These studies showed that lungs from IPF patients present a clear enhancement of 18 F-FDG uptake, with an excellent short-term reproducibility (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…These studies showed that lungs from IPF patients present a clear enhancement of 18 F-FDG uptake, with an excellent short-term reproducibility (11)(12)(13)(14). However, it is actually not known whether 18 F-FDG uptake is related to the severity of the fibrotic process and could be exploited for early assessment of antifibrotic therapies.…”
mentioning
confidence: 99%
“…Metabolically (specifically, glycolysis) active cells have a higher rate of 18 F-FDG uptake and therefore have a higher accumulation of 18 F-FDG, which distinguishes them from quiescent normal cells on PET scans. 18 F-FDG PET is a sensitive imaging modality for the detection of cellular glucose uptake in rabbit models of lung inflammation and fibrosis as well as in human IPF (32,33). PET scans have shown that lung uptake of 18 F-FDG after intravenous injection was increased in microcrystalline silica-or BLM-treated rabbits compared with control rabbits, and the 18 F-FDG signals persisted for several weeks in the lung (34).…”
Section: Nuclear Imaging and Multimodality Imagingmentioning
confidence: 99%